Expanding the phenotype of THRB: a range of macular dystrophies as the major clinical manifestations in patients with a dominant splicing variant - Fernández-Suárez, Elena; González-del Pozo, María; García-Núñez, Alejandro; Méndez-Vidal, Cristina; Martín-Sánchez, Marta; Mejías-Carrasco, José Manuel; Ramos-Jiménez, Manuel; Morillo-Sánchez, María José; Rodríguez-de la Rúa, Enrique; Borrego, Salud; Antiñolo, Guillermo (Frontiers in Cell and Developmental Biology, 2023)
Inherited retinal dystrophies (IRDs) are a clinically and genetically heterogeneous group of disorders that often severely impair vision. Some patients manifest poor central vision as the first symptom due to cone-dysfunction, which is consistent with cone dystrophy (COD), Stargardt disease (STGD), or macular dystrophy (MD) among others. Here, we aimed to identify the genetic cause of autosomal dominant COD in one family. WGS was performed in 3 affected and 1 unaffected individual using the TruSeq Nano DNA library kit and the NovaSeq 6,000 platform (Illumina). Data analysis identified a novel spliceogenic variant (c.283 + 1G>A) in the thyroid hormone receptor beta gene (THRB) as the candidate disease-associated variant. Further genetic analysis revealed the presence of the same heterozygous variant segregating in two additional unrelated dominant pedigrees including 9 affected individuals with a diagnosis of COD (1), STGD (4), MD (3) and unclear phenotype (1). THRB has been previously reported as a causal gene for autosomal dominant and recessive thyroid hormone resistance syndrome beta (RTHβ); however, none of the IRD patients exhibited RTHβ. Genotype-phenotype correlations showed that RTHβ can be caused by both truncating and missense variants, which are mainly located at the 3′ (C-terminal/ligand-binding) region, which is common to both THRB isoforms (TRβ1 and TRβ2). In contrast, the c.283 + 1G>A variant is predicted to disrupt a splice site in the 5′-region of the gene that encodes the N-terminal domain of the TRβ1 isoform protein, leaving the TRβ2 isoform intact, which would explain the phenotypic variability observed between RTHβ and IRD patients. Interestingly, although monochromacy or cone response alterations have already been described in a few RTHβ patients, herein we report the first genetic association between a pathogenic variant in THRB and non-syndromic IRDs. We thereby expand the phenotype of THRB pathogenic variants including COD, STGD, or MD as the main clinical manifestation, which also reflects the extraordinary complexity of retinal functions mediated by the different THRB isoforms.